CHARACTERIZATION OF FEW MEDICINAL PLANTS FROM SOUTHERN ORISSA FOR THEIR FREE RADICAL SCAVENGING PROPERTY. - ROJITA MISHRA; SATPAL SINGH BISHT (International Journal of Pharma and Bio Sciences, 2012)
Free radicals and reactive oxygen species are generated in the body due to various physiological and biochemical processes. They are responsible for various chronic diseases like cancer, diabetes and oxidative damage of DNA and proteins. There is a huge demand of herbal antioxidant compounds in the market. Padaeria foetida,Tribulus terrestris and Oxalis corniculata are used in traditional healthcare system to cure various diseases. During the present investigation the biochemical profiling and In vitro free radical scavenging activity of methanolic extract of the selected plants have been studied. Total polyphenol content was found highest in Paederia foetida( 35.67mg of gallic acid equivalent per gram of the extract) followed by Tribulus terrestris(25.67 mg of gallic acid/gram of the extract) and Oxalis corniculata extracts .(16.87 mg of gallic acid/gram of the extract). The IC50 value of the Padaeria foetida,Tribulus terrestris and Oxalis corniculata 21.32 µg/ml,22.87 µg/ml and 32.78 µg/ml respectively.